Game-Based Vocabulary Learning: The Effectiveness of Spelling Bee in EFL Instruction - Muh. Tedy Firansyah; Adi Isma; Ahyadi Ahyadi (Innovations in Language Education and Literature, 2026)
Vocabulary acquisition remains a persistent challenge in EFL classrooms, particularly where students have minimal exposure to English outside school. Conventional instructional methods often fail to sustain motivation or produce meaningful vocabulary gains. This study examines the effectiveness of the Spelling Bee Game as a game-based vocabulary learning strategy among eighth-grade students at SMPN 4 Pamboang, West Sulawesi, Indonesia. A quasi-experimental pre-test and post-test control group design was employed, involving 39 students divided into an experimental class (n=19) and a control class (n=20). The experimental group received vocabulary instruction through three Spelling Bee variations, while the control group followed conventional methods. Data were gathered through vocabulary tests and a Likert-scale questionnaire measuring learning interest. Results showed that the experimental group's mean score rose substantially from 46.6 to 79.5, compared to a modest gain from 47.25 to 66.5 in the control group. An independent sample t-test confirmed a statistically significant difference (Sig. = 0.000). The questionnaire yielded an overall average of 86.2%, classified as Excellent, indicating strong student interest in the approach. These findings suggest that Spelling Bee Game offers a viable and engaging alternative to conventional vocabulary instruction in low-exposure EFL settings.